GHEORGHE CUCU – THE COMPOSER'S CREATIONS IN MANUSCRIPT - IONAȘCU, Stelian (Studia Universitatis Babes-Bolyai Musica, 2018)
In 1970, I.B.M.B.O.R. (The Missionary Biblical Institute of the Romanian Orthodox Church) published “Hymns of the Divine Liturgy arranged for mixed chorus”. This work contains only 50 hymns – just a small section of the composer’s creation. Nicolae Lungu, the author of the foreword on this edition, mentioned: “many hymns were issued in booklets, handbooks and musical periodicals; other hymns were preserved in manuscript, waiting to be published” (Gheorghe Cucu, Cântările Sfintei Liturghii..., (Holy Liturgy Songs...), Bucharest, 1970, p. IV). In this study we refer to the manuscripts kept in the Romanian Academy Library. Albeit much of Cucu’s musical scores were published and were shared by most of the Romanian and Diaspora choirs, there still remains an unexplored part of Cucu’s creation that completes the image of his personality as composer, conductor and professor.